Because of Winn-Dixie - DiCamillo, Kate.; local (London : Walker Books, 2001)
Ten-year-old India Opal Buloni describes her first summer in the town of Naomi, Florida, and all the good thin.
Book Links (A.L.A.), May 2000.
Booklist, March 2001.
Horn Book, July 2000.
Kirkus Starred, April 2000.
New York Times, May 2000.
Notable/Best Books (A.L.A.), January 2001.
Keywords: Newbery Medal/Honor, 2001.; sears; sears -- Dogs; sears -- City and town life -- Florida; sears -- Florida